HDL metabolism and functions impacting on cell cholesterol homeostasis are specifically altered in patients with abdominal aortic aneurysm - Adorni, Maria Pia; Palumbo, Marcella; Marchi, Cinzia; Zimetti, Francesca; Ossoli, Alice; Turri, Marta; Bernini, Franco; Hollan, Ivana; Moláček, Jiří; Treska, Vladislav; Ronda, Nicoletta (Frontiers in Immunology, 2022)
Background: the aetiopathogenesis of abdominal aortic aneurysm (AAA) is still unclarified, but vascular inflammation and matrix metalloproteases activation have a recognized role on AAA development and progression. Circulating lipoproteins are involved in tissue inflammation and repair, particularly through the regulation of intracellular cholesterol, involved in cell damage and pro-inflammatory activation. We analyzed lipoprotein metabolism and function in AAA and in control vasculopathic patients, to highlight possible non-atherosclerosis-related, specific abnormalities. Methods: we measured fluorimetrically serum esterified/total cholesterol ratio, as an index of lecithin-cholesterol acyltransferase (LCAT) activity, and cholesteryl ester transfer protein (CETP) activity in patients referred to vascular surgery either for AAA (n=30) or stenotic aortic/peripheral atherosclerosis (n=21) having similar burden of cardiovascular risk factors and disease. We measured high density lipoproteins (HDL) cholesterol efflux capacity (CEC), through the ATP-binding cassette G1 (ABCG1) and A1 (ABCA1) pathways and serum cell cholesterol loading capacity (CLC), by radioisotopic and fluorimetric methods, respectively. Results: we found higher LCAT (+23%; p < 0.0001) and CETP (+49%; p < 0.0001) activity in AAA sera. HDL ABCG1-CEC was lower (-16%; p < 0.001) and ABCA1-CEC higher (+31.7%; p < 0.0001) in AAA. Stratification suggests that smoking may partly contribute to these modifications. CEC and CETP activity correlated with CLC only in AAA. Conclusions: we demonstrated that compared to patients with stenotic atherosclerosis, patients with AAA had altered HDL metabolism and functions involved in their anti-inflammatory and tissue repair activity particularly through the ABCG1-related intracellular signaling. Clarifying the relevance of this mechanism for AAA evolution might help developing new diagnostic parameters and therapeutic targets for the early management of this condition.